Manipulation tactics within family: behavioral-genetic perspective - Butković, Ana; Bratko, Denis (2011)
Manipulation tactics represent different ways people try to influence others to do something for them. Research has examined manipulation tactics people use in both formal (e.g. at work) and in informal relationships (e.g. family and friends). Studies presented here are exploring sources of individual differences in manipulation tactics using behavioral-genetic designs. Manipulation tactics measure was constructed for this purpose to assess manipulation tactics used between family members. The instrument measures three types of manipulation tactics: indirect tactics for coercion (ITC), direct tactics (DT) and indirect tactics for humoring (ITH). Total score (TM) is also obtained. Family study using parents and their adolescent offspring showed there is familial aggregation of manipulation tactics and suggested that 20-40% of individual differences in manipulation tactics could be attributed to genetic factors. Twin study using 338 twin pairs (105 MZ, 119 DZ, 114 DZO) aged between 15 and 22 years also indicated that individual differences in manipulation tactics could be explained by genetic and environmental factors. Results from both univariate and multivariate model-fitting suggested that genetic factors are the most important for ITH (47-56%), the least for DT (24-28%), while for ITC both genetic (32-37%) and common environmental influences (17-21%) seem to be important.
Projekt MZOS
ENG